1998
DOI: 10.1111/j.2042-3306.1998.tb04099.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of anthelmintic resistance on Danish horse farms, using 5 different methods of calculating faecal egg count reduction

Abstract: Summary This study reports on the prevalence of anthelmintic resistance in strongyles of horses in Denmark. Of 5 methods used for the calculation of faecal egg count reduction (FECR) the method recommended by the World Association for the Advancement of Veterinary Parasitology, for the detection of resistance in sheep was the most sensitive procedure for detecting resistance. Using this method benzimidazole resistance was detected on 33 of 42 farms (79%) examined. Pyrantel was tested on 15 farms and FECR tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 15 publications
5
48
0
1
Order By: Relevance
“…Initially, most reports of BZ resistance were from single farm observations in isolated geographic areas. More recently, multi-farm prevalence studies in the United States and Europe have demonstrated a prevalence of resistance to BZ of 75% or greater [19,25,40,51,81,82,90,101,106]. In many areas, resistance to BZ anthelmintics is now so common that it is difficult to find populations of cyathostomes that are not BZ-resistant.…”
Section: Resistance To Benzimidazolesmentioning
confidence: 99%
See 4 more Smart Citations
“…Initially, most reports of BZ resistance were from single farm observations in isolated geographic areas. More recently, multi-farm prevalence studies in the United States and Europe have demonstrated a prevalence of resistance to BZ of 75% or greater [19,25,40,51,81,82,90,101,106]. In many areas, resistance to BZ anthelmintics is now so common that it is difficult to find populations of cyathostomes that are not BZ-resistant.…”
Section: Resistance To Benzimidazolesmentioning
confidence: 99%
“…Pyrantel-resistant cyathostomes have been reported throughout the southeastern United States [12,71,90,106] as well as in Norway [51] and Denmark [19]. Since lower anthelmintic efficacies should delay the selection for resistance [3], it may be that the relatively lower efficacy of pyrantel [18,67] has delayed the appearance of resistant worms [21].…”
Section: Resistance To Pyrantelmentioning
confidence: 99%
See 3 more Smart Citations